Polymorphic Subtyping for Effect Analysis: the Algroithm - Nielson, Flemming; Nielson, Hanne Riis; Amtoft, Torben (DAIMI Report Series, 1996)
We study an annotated type and effect system that integrates <kbd>let</kbd>-polymorphism, effects, and sybtyping into an annotated type and effect system for a fragment of Concurrent ML. First a type inference algorithm and a procedure for constraint normalisation and simplification are defined, and next they are proved syntactically sound with respect to the annotated type and effect system.